Photophobia and allodynia in persistent post-traumatic headache are associated with higher disease burden - Cortez, Melissa M; Millsap, Leah; Rea, Natalie A; Sciarretta, Christopher; Brennan, KC (Cephalalgia, 2021)
Objective To assess photophobia and allodynia in subjects with post-traumatic headache and examine how these sensory hypersensitivities associate with clinical measures of disease burden. Background Post-traumatic headache is the most frequent and disabling long-term consequence of mild traumatic brain injury. There is evidence of sensory dysfunction in acute post-traumatic headache, and it is known from other headache conditions that sensory amplifications correlate with more severe disease. However, systematic studies in post-traumatic headache are surprisingly scarce. Methods We tested light and tactile sensitivity, along with measures of disease burden, in 30 persistent post-traumatic headache subjects and 35 controls. Results In all, 79% of post-traumatic headache subjects exhibited sensory hypersensitivity based on psychophysical assessment. Of those exhibiting hypersensitivity, 54% exhibited both light and tactile sensitivity. Finally, sensory thresholds were correlated across modalities, as well as with headache attack frequency. Conclusions In this study, post-traumatic headache subjects with both light and tactile sensitivity had significantly higher headache frequencies and lower sensitivity thresholds to both modalities, compared to those with single or no sensory hypersensitivity. This pattern suggests that hypersensitivity across multiple modalities may be functionally synergistic, reflect a higher disease burden, and may serve as candidate markers of disease.